GENDER EQUALITY IN SOCIO-ENVIRONMENTAL EDUCATION - A.A., Adegboye (European Scientific Journal, ESJ, 2012)
Gender equality and sustainability in the use of natural resources are two of a side of the same coin. Claims of sex-based superiority reflect the same mentality as hostile approach that humanity has taken toward nature which has led mankind to subjugate and exploit nature to satisfy human needs instead of comprehending that as part of the greater whole. Humanity must seek to live in harmony with nature. Proposing a shift in paradigm, the paper discusses the need for new methodologies and approaches in education to achieve the goal of harmonious co-existence between sexes. This paper examines a number of issues surrounding cultural change, proposing the implementation of a liberating approach to socio-environmental education based on equality in gender and a balance between "masculine" and "feminine".